2021
DOI: 10.3390/diagnostics11122345
|View full text |Cite
|
Sign up to set email alerts
|

The Shape of Nasopalatine Canal as a Determining Factor in Therapeutic Approach for Orthodontic Teeth Movement—A CBCT Study

Abstract: The aim of this study was to evaluate the impact of the nasopalatine canal (NPC) shape and its morphometric characteristics on expected teeth movement by assessing the distance to maxillary central incisors (MCIs) according to NPC type. The retrospective study was performed on 133 CBCT images. The following parameters were obtained: the antero-posterior diameter (A-P) of the nasal foramen (NF), canal length, A-P and mediolateral diameter (M-L) of the incisive foramen (IF), and the distance between NPC and MCIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 46 publications
(75 reference statements)
0
21
0
Order By: Relevance
“…Large individual variations in the anatomical morphology of the IC exist [54]. Arnaut et al [60] reported that different shapes of the sagittal cross-section of the IC, such as funnel, cylindrical, and hourglass shapes, are associated with the distance to the MCI, and they concluded that different shapes could be a regression limiting factor for the MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Large individual variations in the anatomical morphology of the IC exist [54]. Arnaut et al [60] reported that different shapes of the sagittal cross-section of the IC, such as funnel, cylindrical, and hourglass shapes, are associated with the distance to the MCI, and they concluded that different shapes could be a regression limiting factor for the MCI.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the distance between the root and the wall of IC increases with the increase in height. At the root tip, the distance from the incisive canal is the furthest, and the diameter of the incisive canal is smaller than the distance between the roots of bilateral upper central incisors at this level 15,17 . Therefore, the most dangerous place is the mesial palatal side of the root 1/3, not the apex.…”
Section: Influence the Design Of Orthodontic Treatment Plan And The A...mentioning
confidence: 96%
“…Among them, the distance of the cylindrical shape is the largest, while the distance of the banana-shaped shape is the smallest. Therefore, it is believed that among the four types mentioned above, banana-shaped patients are the most prone to root resorption 17 .…”
Section: Shape and Position Of The Incisive Canalmentioning
confidence: 99%
“…Moreover, another studies using CBCT in anterior maxilla analyze that detection of various anatomic structures, may be useful in the prevention of complications during surgical intervention, as implant placement (49,57). Still, the morphological observed algorithms of the anterior maxilla may offer detailed information that can be used for planning orthodontic teeth movement (58). The justification of CBCT for preoperative implant plan is based on accurate information about vital structures, height, and width of bone, bone density, and alveoli profile (51,59,60).…”
Section: Cone Beam Computed Tomography (Cbct) In Presurgical Evaluati...mentioning
confidence: 99%